Disparities in Income Levels and Violence against Women among Intimate Partners in Informal Settlements in Nakuru County, Kenya: A Case of Jimmia Rescue Centre - Asmani, Beverly Lusike; Gesami, Rachel; Muhingi, Wilkins Ndege (International Journal of Developing Country Studies, 2023)
Purpose: Intimate Partner Violence is on the rise in developing countries and is alarming in Kenya specifically, therefore this study will establish the relationship between disparities in income levels and violence against women among intimate partners in Nakuru County, Kenya; A case of Jimmia Rescue Centre. Resource Theory founded by Goode in 1971 and Gendered Resource Theory founded by Atkinson and Greenstein in 2005 anchored this study. Methodology: Embedded mixed method was employed which consisted of descriptive survey and phenomenological designs for quantitative and qualitative enquiries respectively. The study was conducted in Nakuru County, specifically in Jimmia Rescue center located in Nakuru East. A total sample of 112 respondents from Jimmia Rescue center were sampled through proportionate and purposive techniques. Questionnaires and semi-structured interviews were used to collect data. Qualitative data was grouped, coded, and placed in different categories by selecting similar issues, then assembled analyzed and interpreted. Statistical Package for Social Sciences (SPSS) version 22 for windows was used for coding and keying in data. The results were presented using tables, themes, quotes, and narrative descriptions. Findings: The study established that the majority of the Intimate Partner Violence victims were married as reported by 54 out of 90 (60%) respondents and 66 out of 90 (73% ) of the respondents were from monogamous marriages. The study also established 53% of the women victims were unemployed, income levels and unemployment status influenced violence against women. Violence was experienced in households where 80% respondents reported that earnings was controlled by husbands. This study concluded that Intimate Partner Violence is a concern among married women especially those in monogamous marriages and unemployed. Unique contribution to theory, practice and policy: The study recommends couples to work towards equal contribution in gender roles and contributing household income to reduce power imbalances that contribute to Intimate Partner Violence